The Impact of Memorisation Strategy Use in IELTS Speaking Tests for Sub-Band 5.5-6.5 Chinese Candidates - Yang, Kaipei (2024)
This study mainly discusses the impact of memorisation strategy in IELTS speaking among Chinese candidates in the UK. To be specific, it first analyse the correlation of memorisation strategy and predictive validity of IELTS speaking. Second, the effectiveness of memorisation strategy in improving IELTS speaking scores is investigated. Third, it reveals the the way that memorisation strategy affects candidates’ communicative competence in the UK. Mixed Methods of quantitative and qualitative research were employed to have overall data to analyse the research questions. 22 participants who are from different majors in a UK university participated in the questionnaire and 5 of them had interviews. The findings showed that the memorisation strategy and the restriction of interview task in IELTS result in decreased predictive validity in IELTS speaking. In addition, the effectiveness of memorisation strategy in improving IELTS speaking scores is evident because the strategy helps them gain more fluency and accuracy in the speech and it also eases the anxiety during the test. Lastly, the memorisation strategy improves communicative competence including sociolinguistic competence, formulaic competence, discourse competence and linguistic competence. In a nutshell, memorisation strategy is generally useful in IELTS speaking. In terms of real-life conversations, this strategy tends to be less practical than in the test, so candidates need to combine other strategies in the communication.